TARI RUDAT ANAK LEMBAH GUNUNG RINJANI - Mohzana; Hary Murcahyanto; Ainul Faizin (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2022)
This study aims to describe the structure of the form, meaning, and function of motion in the Rudat Dance of the Selaparang Anak Lembah Gunung Rinjani in Aik Dewa Village, Kec. Pringgasela. The method used in this research is a descriptive method with a qualitative research form. The data in this study were observational data, documentation, and oral data from interviews. The data sources in this study were visuals of Rudat dance, videos, and informants. The technique used in this research is observation technique, documentary study, and interview. The data analysis technique was carried out through the stages of data reduction, data presentation, and data conclusion. The results of this study show that the movement of the Rudat Dance in the Selaparang Anak Lembah Gunung Rinjani has 10 forms of structure ranging from the Beronjong movement to the Apologizing movement and each has a different meaning. The function of this Rudat dance is as a medium of propaganda, a means of entertainment or spectacle, and a means of education. Keywords: form, function, the meaning of motion, Rudat dance Abstrak Penelitian ini bertujuan untuk mendeskripsikan struktur bentuk, makna, dan fungsi gerak pada Tari Rudat Sanggar Selaparang Anak Lembah Gunung Rinjani di Desa Aik Dewa Kec. Pringgasela. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan bentuk penelitian kualitatif. Data dalam penelitian ini adalah data obsevasi, dokumentasi dan data lisan hasil wawancara. Sumber data dalam penelitian ini adalah visual tarian Rudat, video, dan informan. Teknik yang digunakan dalam penelitian ini adalah teknik observasi, studi dokumenter dan wawancara.  Teknik analisis data dilakukan melalui tahap reduksi data, penyajian data, dan menyimpulkan data. Hasil dari penelitian ini bahwa gerak Tari Rudat di Sanggar Selaparang Anak Lembah Gunung Rinjani memiliki 10 struktur bentuk mulai gerak Beronjong sampai dengan gerakan Meminta maaf dan masing-masing memiliki makna yang berbeda. Fungsi tari Rudat ini adalah sebagai media dakwah, sarana hiburan atau tontonan, dan sarana pendidikan.